Blogging and using a blog as a means of developing the communication skills of physics teachers (Journal of Educational Sciences, 2024)
In the modern education system, it is impossible to imagine the learning process without using the Internet, which has become an indispensable tool for all subjects of education. At the moment, the participants of the educational process widely use modern technologies as a basis for the transfer and accumulation of knowledge.In this regard, the technology of blogging and using an educational blog on the Internet is gaining popularity, which allows the teacher to plan the learning process more effectively, as well as summarize and evaluate its results.Since blogs offer wide opportunities for communication between people united by common interests, it is advisable to use them as a means of developing communication skills. However, not every teacher today has the skills and knowledge in the field of information technology sufficient to effectively blogging and using an educational blog.The purpose of this study was to determine the attitude of Physics teachers working in secondary education organizations of the Zhetysu region of the Republic of Kazakhstan to the need to blogging and using a blog as a means of developing communication skills. 116 Physics teachers took part in the study. The survey method was used in the study. When processing the results, the frequency of responses and percentages for each response are counted. As a result of the conducted research, it was revealed that the majority of teachers surveyed favorably relate to the blogging and using an educational blogs in Physics lessons along with traditional teaching tools. The necessity of conducting training seminars and courses on the blogging and using an educational blog at the level of educational organizations has also been identified in order for Physics teachers to form an understanding of the principles and methods of blogging and using a blog. The article also reveals the need to develop educational blog management strategies for teachers to understand how to integrate, use and maintain an educational blog in teaching Physics, as well as the effective use of time and effort when blogging. In addition, it is concluded that it is necessary to continue research on solving problems that teachers may have when blogging and using an educational blog as an additional tool in teaching Physics.Key words: educational blog, communication skills, information and communication technologies, educational process, quality of education, teaching Physics, information learning tools.